Contesting transcultural trends: emerging self-identities and urban art images in Hong Kong - Valjakka, Minna (Routledge handbook of graffiti and street art, 2016)
Hong Kong1 is transnational and transcultural by nature. The trends in visual and popular culture - are constantly shaped by people and vogues flowing through the
Gesehen am 15.09.2020